OP40 First Case Of Disinvestment Using Real-World Evidence In Brazil. (2017) - de Lemos, Livia Pires; Guerra, Augusto; Pereira, Ramon; Gomes, Rosangela; Godói, Isabella; Diniz, Isabela; Zimmermann, Ivan; Santos, Marisa; Bennie, Marion; Godman, Brian; Canuto, Vania; Petramale, Clarice; et al.
Abstract : INTRODUCTION: Beta-interferons are used as first-line therapy for relapsing-remitting multiple sclerosis in Brazil. In order to evaluate the possible inferiority of one of the beta-interferons available and support a guideline update, we conducted an eleven-year (January 2000 to December 2010) nationwide real-world performance assessment using the Unified Health System (SUS) databases. METHODS: We assessed whether patients using subcutaneous beta-interferon switched treatment, relapsed or died (composite event) earlier than patients using intramuscular beta-interferons. Patients without a dispensing registry longer than three months were censored. We used the Kaplan-Meier method to estimate the cumulative probability of persistence on initial treatment, and compared groups with the Log-rank test. The influence of the drug on the occurrence of event was assessed with Cox proportional hazards analysis. RESULTS: The number of patients included was 12, 154, and the majority started treatment with subcutaneous beta-interferon-1a (45.7 percent), followed by subcutaneous beta-interferon-1b (27.7 percent) and by intramuscular beta-interferon (26.6 percent). Women represented 73.1 percent and the mean age was 38.93±11.34 years old. The group of patients who used intramuscular beta-interferon switched treatment, relapsed or died earlier (median 47 months; 95 percent Confidence Interval, CI 44–52) than patients using the subcutaneous beta-interferons, (69 months (95 percent CI 64–76) for beta- interferon 1a and 73 (95 percent CI 66–84) months for beta-interferon 1b) (p< .0001 for both comparisons). Accordingly, the use of intramuscular beta-interferon was associated with a higher probability of event (Hazard ratio, HR 1.38; 95 percent CI 1.29-1.48), while the use of the other beta-interferons had a protective effect (1a: HR .86; 95 percent CI .81-.92; 1b: HR .89; 95 percent CI .83-.95). CONCLUSIONS: The inferiority of intramuscular beta-interferon found in the real-world corroborates findings from head-to-head studies and systematic reviews conducted by Cochrane and the National Commission for Technology Incorporation in SUS (CONITEC/Brazil). This result led to disinvestment in intramuscular beta-interferon and was the first case of clinical guideline update using real-world evidence in Brazil.